0131 Taking risks and survival jobs: foreign-born workers and work-related injuries in Australia. (23rd June 2014) - Reid, Alison; Lenguerrand, Erik; Santos, Iracema; Read, Ursula; LaMontagne, Anthony; Fritschi, Lin; Harding, Seeromanie
Abstract : Objectives: Higher rates of work-related injuries (WRI) have been reported among foreign-born workers in many countries, but little is known about the situation in Australia. The aim of the study was to examine WRI among foreign-born workers in Australia. Method: This was a two phase mixed methods study. The first stage used the 2005/6 and 2009/10 Australian national Multi-Purpose Household Survey (MPHS) information on WRI occurring in the previous year (N = 36 702). Logistic regression examined the relationship between WRI and region of birth (Australia born =baseline), and whether the effect varied by period of arrival in Australia, age, sex, industry and working conditions. In the second stage, purposively sampled foreign-born workers and stakeholders from 22 countries took part in individual interviews (n = 17) or focus groups (n = 75). A concurrent thematic analysis was conducted. Results: In the MPHS, more WRI were reported by workers in agriculture, manufacturing, construction, hospitality and transport industries than in the service industry, and by those in unfavourable working conditions (e.g. unpaid leave). Migrant status, regardless of region of birth, was generally not associated with higher WRI reporting. Qualitative interviews suggested that understanding and practice of Occupational Health and Safety (OH&S) was influenced by education, skill level, job security, dependent relatives in home countries and by social ties in communities. Conclusions: Whereas the MPHS point to higher risks related to area of work rather than migrant status, qualitative interviews suggest under-reporting of WRI among low income migrants mainly due to fear of losing their jobs.